2016
DOI: 10.3390/ijms17081212
|View full text |Cite
|
Sign up to set email alerts
|

Design of Phosphonated Imidazolium-Based Ionic Liquids Grafted on γ-Alumina: Potential Model for Hybrid Membranes

Abstract: Imidazolium bromide-based ionic liquids bearing phosphonyl groups on the cationic part were synthesized and grafted on γ-alumina (γ-Al2O3) powders. These powders were prepared as companion samples of conventional mesoporous γ-alumina membranes, in order to favor a possible transfer of the results to supported membrane materials, which could be used for CO2 separation applications. Effective grafting was demonstrated using energy dispersive X-ray spectrometry (EDX), N2 adsorption measurements, fourier transform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
29
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(31 citation statements)
references
References 42 publications
2
29
0
Order By: Relevance
“…This image also illustrated nano-spaces between the particles which are very good places for successful immobilization and adsorption of different chemical compounds. The X-ray diffraction (XRD) analysis also demonstrated a broad peak between 2 theta of 20-40 degree that is characteristic of wellorganized organosilica materials ( Figure 7) [36].…”
Section: Resultsmentioning
confidence: 99%
“…This image also illustrated nano-spaces between the particles which are very good places for successful immobilization and adsorption of different chemical compounds. The X-ray diffraction (XRD) analysis also demonstrated a broad peak between 2 theta of 20-40 degree that is characteristic of wellorganized organosilica materials ( Figure 7) [36].…”
Section: Resultsmentioning
confidence: 99%
“…3,4,10,11 In our previous studies we demonstrated that g-alumina can be graed with two imidazolium bromide-based ionic liquids bearing phosphonyl groups on the cationic part (either dialkyl or bis(trimethylsilyl)ester phosphonate) under specic reaction conditions. 15 The graing process was found to be timedependent and the possible formation of bulk aluminum phosphonate phases was avoided. In the conclusion of this study, the applied reaction conditions with the dialkylphosphonate-based IL ([ImPE][Br]) were found to be the most promising route for graing the surface of g-alumina supports.…”
Section: Introductionmentioning
confidence: 99%
“…In the conclusion of this study, the applied reaction conditions with the dialkylphosphonate-based IL ([ImPE][Br]) were found to be the most promising route for graing the surface of g-alumina supports. 15 In this work, the following four ILs were studied ( to be promising coupling agents for CO 2 transport applications. As shown in Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Aluminum oxide, commonly called alumina, has tremendous applications in ceramics, medical products, and catalysis, to name a few [1][2][3][4][5][6]. Despite the expanding number of applications for aluminum oxide, the physical arrangement and interactions of liquids at Al 2 O 3 surfaces remains poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…In this way, changes in band frequencies and intensities may be used to infer changes in the local structures of the ions. Many spectroscopic studies on ionic liquid interactions with nanostructured metal oxides focus on changing the temperature of the composite or varying the molecular structure of the ionic liquid in contact with the solid (e.g., lengthening the alkyl side chain) to probe the interfacial interactions [1][2][3][4][5][6][7][8][9]. Hydrostatic pressure is another degree of freedom that can continuously tune the structures, interactions, and solvation of chemical systems.…”
Section: Introductionmentioning
confidence: 99%